Hubungan Perencanaan Karir dengan Kesiapan Kerja pada Mahasiswa Tingkat Akhir Berpengalaman Magang - Tjenita Young; Zamralita Zamralita; Ismoro Reza Prima Putra (YASIN, 2026)
Recent phenomena indicate that many final-year university students remain insufficiently prepared for the transition to the workforce despite having internship experience, underscoring the importance of internal factors such as career planning in shaping work readiness. This study aimed to examine the relationship between career planning and work readiness among final-year students with internship experience. A quantitative, non-experimental correlational design was employed, using purposive sampling to recruit 192 final-year students from various faculties who had completed an internship. The instruments used were a career planning scale adapted from Gould and a work readiness scale developed by Indah based on Pool and Sewell’s theory, with data collected online via a digital questionnaire. The analysis showed a significant positive relationship between career planning and work readiness, rs(190) = .59, p < .001, indicating that the higher the level of career planning possessed by students, the higher their work readiness. Thus, it can be concluded that the relationship between the two variables is more strongly influenced by internal factors than by demographic characteristics or internship experience, highlighting the importance of strengthening career planning in preparing students for the transition to the world of work.